Hub cultural y artístico para convertir el vacío fronterizo: una intervención dentro de la Estación de la Sabana y sus Alrededores (2021)
Urban interruptions, directly affect the urban systems of a city, from the pedestrian flows to public transportation flows passing by commercial and services activities. When identifying the site of the Station of the Sa- bana as a scar in the urban texture of the city center of Bogota, a number of authors could be cited when talking about the phenomena, looking at the effects of such area from various point of views such as urban, architectural, social, economical and cultural. This investigation aims to study strategies to convert a Border Vacuum into a cultural and artistic hub taking into consideration the arguments, ideas and theories of authors such as Jane Jacobs who defined the term Border Vacuum and analyses its effect, Francoise Astorg Bollack and Francesco Cherchi who present the opportunity of old abandoned buildings to revive a neighborhood and the relations between the private and public spaces.